Association of genomic variants at PAX8 and PBX2 with cervical cancer risk. Issue 4 (6th May 2021) - Ramachandran, Dhanya; Wang, Yingying; Schürmann, Peter; Hülse, Fabienne; Mao, Qianqian; Jentschke, Matthias; Böhmer, Gerd; Strauß, Hans‐Georg; Hirchenhain, Christine; Schmidmayr, Monika; Müller, Florian; Runnebaum, Ingo; et al.
Abstract: Cervical malignancy is triggered by human papillomavirus infection but the risk for cervical cancer has a hereditary component. From a recent Genome Wide Association Study meta‐analysis, 2q14.1 ( PAX8 ) and 6p21.32 ( PBX2 ) have been proposed as novel cervical cancer susceptibility loci. We investigated the two main signals at these loci in an independent case‐control series of 2578 cases with cervical dysplasia or carcinoma and 1483 healthy females. We find significant associations for both variants, rs10175462 at PAX8 and rs2856437 at PBX2, with overall cervical disease (rs10175462: odds ratio [OR] 0.82, 95% confidence interval [CI] 0.74‐0.91, P = 2.4 × 10 −4 ; rs2856437: OR 1.52, 95% CI 1.14‐2.02, P = .004). Both variants showed evidence of association with invasive squamous cervical cancer (rs10175462 : OR 0.80, 95% CI 0.68‐0.94, P = .006; rs2856437: OR 1.56, 95% CI 1.03‐2.36, P = .036) and with high‐grade dysplasia (rs10175462: OR 0.79, 95%CI 0.70‐0.90, P = 1.9 × 10 −4 ; rs2856437: OR 1.58, 95% CI 1.15‐2.17, P = .005). A combined analysis of high‐grade dysplasia and invasive cervical cancer also showed significant associations for both variants (rs10175462: OR 0.81, 95% CI 0.73‐0.91, P = 2.4 × 10 −4 ; rs2856437: OR 1.57, 95% CI 1.18‐2.10, P = .002). No association was detected for rs2856437 with low‐grade dysplasia, while rs10175462 showed weak evidence of association ( P = .05). RNA analyses in cervical samples revealed that PAX8 transcripts were upregulated in HPV‐positive lesions ( P = .008) but this was not observed in the presence of the protective minor allele of rs10175462. The rs10175462 genotype also correlated with reduced levels of the lncRNA PAX8‐AS1 ( P < .001). Taken together, our results extend the evidence for a link between genomic risk variants at the HLA region ( PBX2 ) with cervical disease and support PAX8 as the first consistent non‐HLA cervical cancer susceptibility locus. Abstract : What's new? High‐risk HPV is a major trigger of cervical cancer, but only some women are susceptible. Here, the authors investigated two genetic variants recently identified in genome‐wide association studies as possibly related to cervical cancer risk. The variants are located in the genes PAX8 and PBX2 . This study tested the association in a German population containing 1122 cases of invasive cervical cancer, 1384 cases of cervical dysplasia, and 1483 controls. Both variants showed an association with cervical cancer and high‐grade cervical dysplasia. RNA analysis also revealed that the PAX8 variants influenced the amount of transcript found in cervical samples.